THE EFFECT OF POLITICAL CONNECTIONS, MULTIPLE DIRECTORSHIPS, COMPANY PERFORMANCE, AND TAX PLANNING ON EARNING MANAGEMENT IN REGISTERED STATE-OWNED COMPANIES AT BEI 2019-2022 - Fizal Alharis; Razif; Mursidah; Muhammad Yusra (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the effect of political connections, multiple directorships, company performance, and tax planning on earnings management. This study used a sample of BUMN companies listed on the IDX in 2019-2022 as many as 44 samples using purposive sampling techniques totaling 11 companies with observations for 4 years. The analysis technique used here is to use multiple linear regression analysis which is processed using the IBM SPSS 26 program. The results of the study using the t test (partial) show that the variables of political connections, multiple directorships, solvency, profitability, and tax planning have no significant effect on the earnings management variable. While the liquidity variable has a significant positive effect on earnings management.